1994
DOI: 10.1002/j.1460-2075.1994.tb06410.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a suicidal DNA repair protein: the Ada O6-methylguanine-DNA methyltransferase from E. coli.

Abstract: The mutagenic and carcinogenic effects of simple alkylating agents are mainly due to methylation at the O6 position of guanine in DNA. O6‐methylguanine directs the incorporation of either thymine or cytosine without blocking DNA replication, resulting in GC to AT transition mutations. In prokaryotic and eukaryotic cells antimutagenic repair is effected by direct reversal of this DNA damage. A suicidal methyltransferase repair protein removes the methyl group from DNA to one of its own cysteine residues. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(203 citation statements)
references
References 39 publications
7
192
1
Order By: Relevance
“…This confirms previous studies in which crude cell extracts of E. coli were used (10 -13) and rules out the possibility that the resistance is due to the rapid metabolism of the O 6 -benzylguanine by bacterial enzymes. The crystal structure of Ada-C suggests that the tryptophan residue at position 336 may limit access to the cysteine acceptor site (6,7). Studies with the human AGT have indicated that a proline residue located 5 residues to the amino side of this cysteine is necessary for optimal reaction with O 6 -benzylguanine (22,23).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This confirms previous studies in which crude cell extracts of E. coli were used (10 -13) and rules out the possibility that the resistance is due to the rapid metabolism of the O 6 -benzylguanine by bacterial enzymes. The crystal structure of Ada-C suggests that the tryptophan residue at position 336 may limit access to the cysteine acceptor site (6,7). Studies with the human AGT have indicated that a proline residue located 5 residues to the amino side of this cysteine is necessary for optimal reaction with O 6 -benzylguanine (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…6 -Benzylguanine-The purified alkyltransferase proteins were incubated in 50 mM Tris-HCl, pH 7.5, 0. 5 mM dithiothreitol, and 0.1 mM EDTA with 5Ј-d(AACAGCCATATa 6 GGCCC)-3Ј in which a 6 G represents O 6 -benzylguanine or O 6 -methylguanine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These highly conserved amino acids are located in the carboxyl half of the protein, which includes the DNA-binding domain and the cysteine acceptor site [9][10][11] (Figure 1). Based on the alkyltransferase crystal structure [12][13][14], models of the binding of the DNA substrate to the protein, and studies of the reaction mechanism [9,15,16], it is likely that the O'-alkylguanine residue is flipped out of the DNA helix and bound in an active-site pocket containing the Cys-145 acceptor.…”
Section: Introductionmentioning
confidence: 99%
“…In eukaryotes the HTH motif is seen in proteins that regulate development and differentiation, transcription factors (TFIIB/ TFIIE) and chromatin proteins (histone H1) (Schultz et al, 1991;Wilson et al, 1992Brennan, 1993Clark et al, 1993;Ramakrishnan et al, 1993;Swindells, 1995;Kodandapani et al, 1996;Aravind and Koonin, 1999;Gajiwala and Burley, 2000). This motif has also been identified in proteins involved in DNA repair and RNA metabolism (Moore et al, 1994;Wah et al, 1997;Selmer and Su, 2002;Alfano et al, 2004;Dong et al, 2004). In addition to DNA binding, the HTH can also be adapted for mediating specific protein-protein interactions or can be part of a structural unit of a large enzymatic domain (Guo et al, 1997;Wong et al, 2000;Zheng et al, 2002).…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%